Association Between Intersectional Stigma and Psychological Well-Being Among Men Who Have Sex with Men Living with HIV. - Mi, Tianyue; Yang, Xueying; Lan, Guanghua; Qiao, Shan; Shen, Zhiyong; Zhou, Yuejiao; Li, Xiaoming (AIDS & Behavior, 2025)
Men who have sex with men (MSM) living with HIV face considerable psychosocial challenges, including stigma and discrimination, which may affect their mental health. Instead of considering each stigmatized identity in isolation, this study investigated the association between intersected HIV- and MSM-related stigma and psychological well-being of MSM living with HIV. Data of 402 MSM living with HIV were collected through a cross-sectional study in Guangxi, China, focusing on the association between HIV-/MSM-related stigma and HIV-related health outcomes among MSM living with HIV. Latent Moderated Structural Equations Approach was employed to examine the moderation effect of MSM-related stigma on the relationship between HIV-related stigma and mental health outcomes. The findings revealed that with a lower level of MSM-related stigma, the associations between HIV-related stigma and depression (β = 0.99, 95%CI [-0.63, 2.61], p = 0.23) or anxiety (β = 1.61, 95%CI [-0.44, 3.65], p = 0.12) were not significant; with a higher level of MSM-related stigma, the association between HIV-related stigma and depression (β = 3.32, 95%CI [1.67, 4.96], p < 0.001) or anxiety (β = 4.95, 95%CI [2.68, 7.22], p < 0.001) showed significant positive associations. The study demonstrates that higher levels of MSM-related stigma can intensify the relationship between HIV-related stigma and depression/anxiety among MSM. By emphasizing the role of intersectional stigma in adverse mental health outcomes, these findings will inform the development of effective and sustainable health strategies, policies, and services, including tailored mental health services and community-led stigma reduction programs aimed at the enhancement of well-being among MSM living with HIV.